Problèmes quotidiens de psychiatrie pénitentiaire à travers les changements du paysage psychiatrique et pénitentiaire français - Lamothe, Pierre (Criminologie, 1988)
The penitentiary psychiatrist, in France, as in Québec and elsewhere is confronted daily with multiple dilemmas of a moral, ethical and practical nature. He/she is obliged to practice within the constraints of laws, policies and regulations which are not necessarily sensitive to the needs of the mentally disordered inmate. The distinction in French law between the “mad” and the “bad”, and the role of the psychiatrist in placing the accused in one or other of these categories is described, as is the penal system, and one regional treatment center for prison inmates. Problems related to the prescription and distribution of medications are presented in order to illustrate the constraints and ethical dilemmas inherent in psychiatric practice within a penal institution.